Meningkatkan Kemampuan Akademik Peserta Didik melalui Penerapan Strategi Pembelajaran Fun Learning pada Mata Pelajaran PAI - Jannah, Miftahul; Rosvianto, Devi; Gusmaneli, Gusmaneli (Faidatuna, 2024)
This article discusses the application of Fun Learning strategies in Islamic Religious Education subjects with the aim of improving students' academic abilities. Fun Learning strategy is an approach that emphasizes a fun and interactive learning atmosphere. Through the literature method, this article analyzes the concept and characteristics of the Fun Learning strategy and its benefits for students in Islamic Education subjects. The results show that the application of Fun Learning strategies can increase interest, motivation, concentration, and understanding of the material, as well as develop students' critical thinking skills, creativity, confidence, and positive character. Some ways of applying Fun Learning strategies include through games, storytelling, humor, charades and pictures. Thus, Fun Learning strategies can be used as an effective alternative to improve the quality of PAI learning and students' academic abilities.